Shape optimization based design of arch-type dams under uncertainties. Issue 9 (2nd September 2018) - Fengjie, Tan; Lahmer, Tom
ABSTRACT: Comparing existing design methodologies for arch-type dams, model-based shape optimization can effectively reduce construction costs and leverage the properties of construction materials. To apply means of shape optimization, suitable variables need to be chosen to formulate the objective function, which is here the volume of the arch dam. A genetic algorithm is adopted as the optimization method, which allows a global search. The reliability index is considered as the main constraint. Its computation is realized by adaptive Kriging Monte Carlo simulation, which visibly increases the analysis efficiency compared with traditional Monte Carlo simulations. Constraints, such as the reliability index and further with respect to the geometry, are taken into consideration by a penalty formulation. By means of this approach, a reliability-based design can be found which ensures both the safety and serviceability of a newly designed arch-type dam.